Beyond the binary: sexual health outcomes of transgender and non-binary service users of an online sexual health service. (September 2021) - Day, Sara; Smith, Joanna; Perera, Sean; Jones, Sophie; Kinsella, Ryan
Sexual health data on transgender and non-binary (TNB) people in the United Kingdom are limited. TNB individuals experience significant socioeconomic and stigma-related disadvantages. Sexual health morbidity and unmet need is likely to be significant. We compared the sexual health outcomes of TNB and cisgender users of London's online sexual health service. Of 119329 users that registered with the e-service between 30.4.19 and 31.12.19, 504 (0.42%) identified as TNB: 302 TNB users requested 463 kits. 78.4% (363/463) of kits were returned. 99.4% of dispatched kits included throat and rectal swabs for gonorrhoea and chlamydia testing. STI/HIV test positivity was: 5.5% syphilis, 4.8% chlamydia, 3.4% gonorrhoea and 0.7% HIV positive. HIV prevalence amongst TNB individuals was: 4.3%. 19.9% of TNB individuals engaged in chemsex, group sex, or fisting and were more likely to engage in sex work. 97.7% gave the service 4/5 or 5/5 star rating. We observed high positivity rates of HIV/STIs amongst TNB individuals and significant levels of high-risk sexual activity. Service users rated the service highly. Given TNB often have complex healthcare needs, some of which cannot be met entirely online, physical clinics must work collaboratively with e-services to support and protect this marginalised population.